BrachyView: Combining LDR seed positions with transrectal ultrasound imaging in a prostate gel phantom. (February 2017) - Alnaghy, S.; Cutajar, D.L.; Bucci, J.A.; Enari, K.; Safavi-Naeini, M.; Favoino, M.; Tartaglia, M.; Carriero, F.; Jakubek, J.; Pospisil, S.; Lerch, M.; Rosenfeld, A.B.; et al.
Highlights: BrachyView is an in-body gamma camera for seed imaging in prostate brachytherapy. Thirty I-125 seeds were reconstructed in a tissue equivalent prostate gel phantom. BrachyView-TRUS image fusion using a mechanical co-registration method is performed. It was observed that 75% of seed positions were reconstructed within 1 mm of CT. Abstract: Purpose: BrachyView is a novel in-body imaging system which aims to provide LDR brachytherapy seeds position reconstruction within the prostate in real-time. The first prototype is presented in this study: the probe consists of a gamma camera featuring three single cone pinhole collimators embedded in a tungsten tube, above three, high resolution pixelated detectors (Timepix). Methods: The prostate was imaged with a TRUS system using a sagittal crystal with a 2.5 mm slice thickness. Eleven needles containing a total of thirty 0.508 U 125 I seeds were implanted under ultrasound guidance. A CT scan was used to localise the seed positions, as well as provide a reference when performing the image co-registration between the BrachyView coordinate system and the TRUS coordinate system. An in-house visualisation software interface was developed to provide a quantitative 3D reconstructed prostate based on the TRUS images and co-registered with the LDR seeds in situ. A rigid body image registration was performed between the BrachyView and TRUS systems, with the BrachyView and CT-derived source locations compared. Results: The reconstructed seed positions determined by the BrachyView probe showed a maximum discrepancy of 1.78 mm, with 75% of the seeds reconstructed within 1 mm of their nominal location. An accurate co-registration between the BrachyView and TRUS coordinate system was established. Conclusions: The BrachyView system has shown its ability to reconstruct all implanted LDR seeds within a tissue equivalent prostate gel phantom, providing both anatomical and seed position information in a single interface.